Weed control with saturated steam in organic highbush blueberry - Moretti, Marcelo L.; Pedroso, Rafael M. (Frontiers in Agronomy, 2023)
Weed management is often a predominant and costly problem in the production of organic blueberries. Geotextile weed fabrics of woven polyethylene are widely used in organic blueberry fields to suppress weeds growing within the rows. Weeds, such as Convolvulus arvensis L., grow at the base of the blueberry plants or through openings and around the edges of the weed fabric, thus requiring hand weeding. This study evaluates the integration of saturated steam (SS), a rotary brush (RB), and organic herbicides for weed control in blueberries. Dose–response studies indicated that SS applied at 121°C and at 7.4 m3 ha−1 of steam (3,655 MJ ha−1) resulted in over 90% control and a reduction in the dry weights of C. arvensis. When treatments were directed to the base of the blueberry plants, SS at 7.4 m3 ha−1 provided 80% control of C. arvensis 28 days after treatment (DAT) and was comparable to hand weeding. Both of these treatments outperformed capric plus caprylic acid (CC) (33.2 kg ai ha−1) or ammonium nonanoate (AN) (24.3 kg ai ha−1) applications, despite C. arversis regrowth being observed. Four repetitive basal applications of SS of up to 29.6 m3 ha−1 over two consecutive years caused minimal and transient damage to new basal shoots of ‘Elliot’ and ‘Duke’ blueberries; basal shoot cross-sectional area compared with the non-treated was unaffected. In contrast, basal application of AN treatments damaged or killed basal shoots. When treatments were applied to the edge of the weed fabric, SS (7.4 m3 ha−1) reduced weed biomass by 42% to 93% at 28 DAT compared with the non-treated. The RB treatment reduced weed biomass from 72% to 99% in all experiments, while CC and AN reduced biomass by 18% to 54%. A partial budget analysis indicated that SS and the RB were 3- and 6.5-fold less expensive than organic herbicides, respectively. Integrating physical (SS) and mechanical (RB) treatments improved weed control. The latter, however, damaged the weed-suppressing fabric where preexisting holes were present, generated dust, and increased the chance of fruit contamination. The SS was safe for the weed-suppressing fabric and the blueberry, but weed regrowth following treatment and copious water requirements hindered its feasibility.